DEVELOPMENT OF ESSAY INSTRUMENT TO MEASURE MATHEMATICAL CONCEPTUAL UNDERSTANDING ON SIMILARITY AND CONGRUENCE: Banten, Indonesia - Wahyu Utomo, Muhammad Faruq; Novaliyosi; Aan Hendrayana; Abdul Fatah (Jurnal Math-UMB.EDU, 2026)
This study aims to develop a valid and reliable essay test instrument to assess mathematical conceptual understanding in ninth-grade junior high school students, focusing on similarity and congruence. Employing a modified 4D model (Define, Design, Develop, Disseminate), the research involved designing a test blueprint based on seven conceptual understanding indicators, expert validation using the Content Validity Ratio (CVR), and field testing to evaluate construct validity, reliability, item difficulty, and discrimination indices. The results indicated that all test items were valid, achieved a high reliability coefficient (α = 0.83), and exhibited varied difficulty and discrimination levels meeting established criteria. Consequently, this instrument is capable of comprehensively measuring students' conceptual understanding and serves as an effective assessment tool in mathematics education. Keywords: Essay Instrument, Mathematical Conceptual Understanding, Similarity and Congruence.